Generative solutions: adaptation and flexibilization in housing as a qualified social response - Gomes, A. C.; Paio, A. (Anais do XIX Congresso da Sociedade Ibero-americana de Gráfica Digital 2015, 2015)
Housing for all is back on the international agenda. The economic crisis forces researchers and architects to rethink the concept of living and adopt more flexible housing design strategies as an alternative to typologies that impose rules of coexistence and do not reflect the social dynamics of a community. The introduction of rules-based housing design strategies allows the implementation of more dynamic processes. This ongoing research is a reflection on the potential of digital tools to develop spatial and formal parameters based on analysis of flexible housing models. This paper presents the initial phase of the research.